Complex intersections : East Asian-Latin American trade linkages in the context of recent multilateral, regional and subregional developments - Scollay, Robert (2000)
Reviews the three principal forms of trade liberalisation embodied in the various existing and possible future trade and economic integration arrangements involving the two regions. Looks at developments under those three approaches up and including the recent proliferation of proposals for preferential trading arrangements. Comments on the relation between regional approaches to liberalisation on the pattern of between the two regions. Identifies some possible future developments in the pattern of regional developments. Explores their possible implications for growth of East Asia-Latin America trade.